Exploration of the slope effect on the uplift capacity of single straight and belled piles supporting transmission towers - Bian, Meihua; Qin, Songlin; Peng, Jianing; Li, Junhua; Zhang, Xingsen (Frontiers in Materials, 2023)
Single piles are normally used to support the transmission tower in mountain areas. Uplift capacity of piles is a key factor in the engineering design to increase the stability of transmission tower foundation. This study numerically investigated the uplift capacity of single straight and belled piles in the sloping ground which consisted of clay layer underlain by medium weathered sandstone. A nonlinear 3D finite element model was proposed to describe the uplift behavior of single piles and was calibrated against a field test on single piles subjected to uplift loading. A parametric study was conducted to investigate the effect of the slope angle (θ) on the uplift behavior of single piles. The uplift capacity decreased as the θ increased for either straight piles or belled piles. Moreover, the range of the equivalent plastic strain was greatest for single piles in the level ground. For piles in the sloping ground, the range of equivalent plastic strain was wider at the position of the downstream slope than that at the position of the upstream slope when the uplift load of single piles reached the maximum. As the expansion angle increased to 30°and 45°, the uplift capacity of belled piles (Ru) was increased by 100% and 180% with respect to that of straight piles, respectively. The increase percentage in the Ru was independent on θ. A practical method was proposed to quantify the slope effect on Ru.